If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -5 + 2 = 6 Reorder the terms: -5 + 2 + -3x = 6 Combine like terms: -5 + 2 = -3 -3 + -3x = 6 Solving -3 + -3x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -3x = 6 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = 6 + 3 -3x = 6 + 3 Combine like terms: 6 + 3 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| 28.95(3)+0.34x=150 | | 10(x-2)+5(x+2)=-10x | | .5=.25+f | | 2x^3+7x^2=-6x | | 1+1/1y+3/4y=-15 | | x+4=17/3+2/3x | | 6z+3z=8z-2 | | 2/5(2x+1)=3(2-4x)+20 | | 1/4-(-5/8) | | -4+14= | | 4x+16=56-5x | | 2h^2-62h+456=0 | | 109-4x=14x+23 | | -1-19=-8v-2v | | cosx-sinx=0.5 | | -1(-y-1)= | | 3n-5=7n-13 | | 14a+9=93 | | -1(-y)= | | 6(15+9)= | | 1y+1=15-3/4y | | y(2y^2-13y-7)=0 | | 0=x^2+kx+2k | | 5ln(5x)=25 | | 9x+2=10y | | 5lnx=15 | | 0.16-0.01(x-2)=-0.03(2-x) | | 8x=27+5x | | 45=6+3x | | 7x+43x+5= | | 2x-(5)=4x | | 1.22x=6.10 |